Rotational invariant image matching based on phase only correlation - Şengür, Abdulkadir; Karabatak, Murat (My University, 2010)
In this work, a rotational invariant image template matching method based on log-polar transform and phase only correlation is presented. The method is composed of two stages. While applying the 2nd Hanning window is formed the first stage, several steps, for phase-based rotational image template matching constitutes the second stage. MATLAB is used for computer simulations. We cropped various image templates for matching purposes. We then rotated that template images with 15, 30 45, 60 and 75 degrees respectively and we saved them. Thus, we obtained totally 60 images for 10 different template images. We finally obtained 93.33% matching accuracy. ©2010 IEEE.
Salt evre i?lintisine dayali döndürmeden ba?imsiz görüntü eşleştirme
18th IEEE Signal Processing and Communications Applications Conference, SIU 2010 -- 22 April 2010 through 24 April 2010 -- Diyarbakir -- 83388
Keywords: Computer simulation; Signal processing; Template matching; Hanning window; Image template matching; Log-polar transform; Phase-only correlation; Rotational invariants; Template images; Two stage; Image matching